RANCANGAN SISTEM INFORMASI IKHTISAR KAS BERBASIS WEB PADA MASJID ULUL ALBAAB BATARANILA DI LAMPUNG SELATAN - Fikri Hamidy; A. Ferico Octaviansyah (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2011)
This research is aimed at (1) finding out the description of the current cash system applied by the mosque; and (2) determining the proposed design of web based cash summary information system for the mosque. The results of the research are (1) It is found that the current cash system used by the mosque is the manual system conducted by the treasurer and treasurer assistant, starting from the existence of the mosque‟s cash receipt and expend evidences. These evidences then become the base of the records in the cash ledger. This cash ledger, functioning as the base for formulating the cash summary, is then rewritten in details into someinterconnected cash ledgers on three information whiteboards with the format: date, detail, amount debit and date, detail, amount credit, in order to show the transparant cash condition to the mosque‟s society;(2) The designed system tested by means of „Black- Box Testing‟ is the web based cash summary information system. This web programming application is engineered to accompany the manual system as a better alternative because it has some strengths in that, it has „Transaction Database‟ which can be processed to produce information with awesome characteristics, i.e. it is neatly ordered, strictly objective, transparant and easily accessible as the mosque‟s society can directly access the dynamic information through the web.